“I Will Not Give You a Penny More Than You Deserve”:Ontario v. Fraser and the (Uncertain) Right to Collectively Bargain in Canada - Braley, Alison (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2011)
This case comment first reviews the jurisprudence that most directly informed the Supreme Court’s ruling in Health Services. Second, this case comment applies the logic underpinning Health Services to the facts of the case at bar. The general argument is that Ontario v. Fraser represents an inconsistent application of two concepts that are central to the understanding of collective bargaining that the SCC had elucidated in Health Services: the meaning of “good faith” and “substantial interference”. The comment concludes that Ontario v. Fraser has narrowed the right to collectively bargain to a greater degree than both proponents and opponents of Health Services might have anticipated.